Diversity Metrics Are Robust to Differences in Sampling Location and Depth for Environmental DNA of Plants in Small Temperate Lakes - Drummond, Jennifer A.; Larson, Eric R.; Li, Yiyuan; Lodge, David M.; Gantz, Crysta A.; Pfrender, Michael E.; Renshaw, Mark A.; Correa, Adrienne M. S.; Egan, Scott P. (Frontiers in Environmental Science, 2021)
Environmental DNA (eDNA) analysis methods permit broad yet detailed biodiversity sampling to be performed with minimal field effort. However, considerable uncertainty remains regarding the spatial resolution necessary for effective sampling, especially in aquatic environments. Also, contemporary plant communities are under-investigated with eDNA methods relative to animals and microbes. We analyzed eDNA samples from six small temperate lakes to elucidate spatial patterns in the distributions of algae and aquatic and terrestrial plants, using metabarcoding of the Internal Transcribed Spacer-1 (ITS1) genomic region. Sampling locations were varied across horizontal and vertical space: sites in each lake included a mixture of nearshore and offshore positions, each of which was stratified into surface (shallow) and benthic (deep) samples. We detected the expected community variation (beta diversity) from lake to lake, but only small effects of offshore distance and sampling depth. Taxon richness (alpha diversity) was slightly elevated in nearshore samples, but displayed no other significant spatial effects. These diversity metrics imply that plant eDNA is more evenly distributed than its generating organisms in these small lake environments. Read abundances were heavily weighted toward aquatic macrophytes, though taxon richness was greatest in the algae and other nonvascular plants. We also identified representatives of many phylogenetically and ecologically varied plant taxa, including terrestrial species from surrounding areas. We conclude that freshwater plant eDNA surveys successfully capture differences among lake communities, and that easily-accessible, shore-based sampling may be a reliable technique for informing research and management in similar ecosystems.